Reactive bone development accompanying to an unextracted root - ERÇALIK YALÇINKAYA, ŞEBNEM; DERGİN, GÜHAN (My University, 2012)
Odontogenic cysts are by far the most common cysts of the jaws. A radicular cyst is a cyst that most likely results when rests of Malassez epithelial cells in the periodontal ligament are stimulated to proliferate and undergo cystic degeneration by inflammatory products from a nonvital tooth. Radiographically, their periphery usually have a well-defined border and their internal structures are radiolucent. In order to make definite radiological diagnosis, more than one projection methods may be needed. The aim of this report is to present a case with an unusual location of radicular cyst caused by a molar root which was left after a tooth extraction procedure and accompanied by reactive bone development.

Çene kemiklerinde en sık görülen kistler odontojenik kistlerdir. Radiküler kist periodontal aralıktaki Malassez epitel artıklarının devital bir dişe ait enflamasyon uyaranlarıyla kistik değişikliğe uğramasıyla oluşan bir kisttir. Radyolojik olarak çevresi belirgin sınırlı ve ortası radyolusenttir. Tanı konulması zor olmamakla birlikte bazen kesin radyolojik tanı için birden fazla görüntüleme yöntemi gerekebilir. Burada amaçlanan diş çekimi sonrası bırakılmış molar diş köküyle birlikte farklı bir lokasyonda görülen reaktif kemik gelişiminin eşlik ettiği radiküler kist vakasını sunmaktır.
Keywords: Tıp; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; Health Sciences; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Araştırma ve Teori; İncelemeler ve Referanslar (tıbbi); Research and Theory; Reviews and References (medical); Odontogenic cyst; reactive bone development; Odontojenik kist; reaktif kemik gelişimi